Patient-centered healthcare service scheduling for patients with multiple conditions - Ji, Jieying (2012)
According to World Health report2000, in year 2000 there is an estimation of 125 million of people suffering from chronic illness and 48% with multiple conditions. By the year 2020, the number of patient will grow to 157 million and 81 million with multiple conditions, an approximation of 52% with multiple conditions. Furthermore, from real case has illustrated that people who are suffering from multiple conditions will require multiple physician visits, redundant activities, long waiting time, conflicting medical advice and unnecessary visit. The above points have highlighted the importance of scheduling of activities which are required by patients who are suffering from multiple conditions according and cater specially for each of the patient.